Interference with NTSR1 Expression Exerts an Anti-Invasion Effect via the Jun/miR-494/SOCS6 Axis of Glioblastoma Cells - Qing Ou-yang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Glioblastoma is the most common and aggressive brain tumor and carries a poor prognosis. Previously, we found that neurotensin receptor 1 (NTSR1) contributes to glioma progression, but the underlying mechanisms of NTSR1 in glioblastoma invasion remain to be clarified. The aim of this study was to investigate the molecular mechanisms of NTSR1 in glioblastoma invasion. Methods: Cell migration and invasion were evaluated using wound-healing and transwell assays. Cell proliferation was detected using CCK-8. The expression of NTSR1, Jun, and suppressor of cytokine signaling 6 (SOCS6) was detected using western blotting. The expression of miR-494 was detected by Quantitative real-time PCR. Chromatin immunoprecipitation assay was performed to examine the interaction between Jun and miR-494 promoter. Dual-luciferase reporter assay and western blotting were performed to identify the direct regulation of SOCS6 by miR-494. An orthotopic xenograft mouse model was conducted to assess tumor growth and invasion. Results: NTSR1 knockdown attenuated the invasion of glioblastoma cells. Jun was positively regulated by NTSR1, which promoted miR-494 expression through binding to miR-494 promoter. SOCS6 was confirmed as a direct target of miR-494, thus, NTSR1-induced miR-494 upregulation resulted in SOCS6 downregulation. Both miR-494 and SOCS6 were involved in the NTSR1-induced invasion of glioblastoma cells. In vivo, tumor invasion and growth were inhibited by NTSR1 knockdown, but were restored with miR-494 overexpression. Conclusion: NTSR1 knockdown inhibited glioblastoma invasion via the Jun/miR-494/SOCS6 axis.